Emblems of Sociality_Transversal social spaces in re-imagining the identity of a modern African city: The case of central Addis Ababa - Berhe, Delina (University of the Witwatersrand, Johannesburg, 2024)
IIIIII Abstract The current African city exists through the lens of global building culture. Addis Ababa, going through immense transformation seems to have taken its architectural inspirations from foreign world-class cities in hopes of reaching global heights. This research explores alternative possibilities to achieve that goal while considering the existing socio-cultural identity of the city. African cities should take their place in the network of globalised cities, however, a sense of representation should be considered to enrich their potential. The transformation of cities through embracing their local ways of life and historical traditions should be prioritized. The work investigates modern city planning in the context of Addis Ababa as its aspirational condition. The overarching theme explores the relationship between the current city planning conditions and their understanding of social space and identity in an Ethiopian context. Specifically, the research is centred in representing identity of social cohesion and its interpretation through architecture and spatial elements. It aims to investigate urban social traditions that have and are being pushed aside within the process of creating a ‘global worthy Addis Ababa’. The study site is central Addis Ababa, Ethiopia, which serves as both the city’s point of origin and locus of ongoing transformations. The work proposes the creation of a Food media library prioritizing indoor and outdoor social spaces, with the goal of fostering a meaningful presence within the evolving cityscape. The research methodology involves analysing historical documents, photo series, mapping and observation of the neighbourhoods and the characters within them. The research aims to create a design in which an overlapping space of critique, knowledge exchange, activity, sense of identity and belongingness can be experienced and transferred. It explores the relationship between diverse societies to create a common space that will be able represent them and create a hub for positive and meaningful interactions. It aims to create a space of contemplation into one’s respected society through nurturing the social dynamics in terms of architectural spaces and interactions.
A research report submitted in fulfillment of the requirements for the Master of Architecture, In the Faculty of Engineering and the Built Environment, Wits of Architecture and Planning, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; Cultural integration; Modern city planning; urban identity; SDG-11: Sustainable cities and communities